(untitled) (Nigerian Journal of Physiological Sciences, 2023)
articular ethnic/racial group. Adiposity measures are employed to screen MRF by clinicians. The ratio of the second to fourth digit of the hand (2D:4D) has been shown to be a tight correlate of MRF. Attempts to predict MRF from hand anthropometry is relatively a new idea. The present study aims to predict MRF from digit and body anthropometry. The study recruited 266 males and 199 females of Hausa origin. Systematic random sampling was employed. Anthropometric measurements and blood pressure were obtained using standard techniques. Regression analysis was used to predict MRF, SPSS version 20 was used for statistical analyses and P < 0.05 was set as level of significance. MRF (serum glucose, total cholesterol, lipoprotein cholesterol, and blood pressure (BP) were predictable from 2D:4D and body anthropometric measures. Waist-to-hip ratio (WHR) was the most consistent MRF predictor. In males, WHR alone predicted TC (R2 = 0.67 and P<0.0001), HDL-C (R2 =0.68 and P <0.0001), LDL-C (R2 = 0.67 and P < 0.001) and diastolic blood pressure (DBP) [R2 =0.43 and P <0.001)]. The right 2D:4D contributed slightly to the prediction of SBP and FBG increasing the R2 value to 0.62from 0.6 for FBG and from 0.6 to 0.64 for SBP Keywords: Body anthropometry, Digit anthropometry, Metabolic risk, Predictability